Holding time in the pressing cycle and its influence on the performance characteristics of zinc oxide varistor discs - Karim, A.N. Mustafizul; Puyane, R.; El-Baradie, M.A; Hashmi, M. S. J. (Elsevier, 1998)
The pressing cycle usually adopted for compacting zinc oxide varistor discs is similar to that followed in the case of conventional ceramic processing. The approach consists of applying force through punches on the powder within the die,employing a number of holding or dwell times in the different phases of loading. Depending on the frictional surface area and the volume of the disc, the total duration of the holding time can be about 20–30% of the pressing cycle. Although there are some specific purposes of these dwell times in obtaining the desired quality of the green body, the resultant effect on the sintered physical and electrical property of the varistor is not reported. The present study was conducted to investigate the impact of the holding time on the performance characteristics. Three input variables, pre-press, press dwell and ejection delay time, were varied at two levels to undertake a factorial design for evaluating the main and interactive effects of these parameters. It has been observed that these dwell times have considerable influences on the physical as well as on the electrical properties of the varistor discs. Thus there is scope for optimizing the level of these pressing parameters to secure enhanced varistor performance.